Prevalence and Factors Associated with Learning Difficulties among University Students in Sarawak, Malaysia - Rahman, Md Mizanur; Jan, Monique Sapong; Sharul, Mohamad; Iyeer, Raasiuen; Vaishnavi (National Journal of Community Medicine, 2024)
Background: University students must learn rapidly and handle complex academic concepts, making it crucial to understand the prevalence of learning difficulties in this population. This study determines the prevalence and factors associated with learning difficulties among university students. Methods: This cross-sectional correlation study was conducted at Universiti Malaysia Sarawak and involved 546 undergraduate students using self-administered questionnaires. IBM SPSS version 28 was used for descriptive and multivariate analysis. Results: The most common difficulties were in expression (33.3%) and general study (34.0%). Age positively correlated with all difficulties, while gender effects were statistically insignificant (p>.05). A positive attitude significantly reduced reading, writing, and calculation difficulties (p<.001), whereas a negative attitude increased expression and general study difficulties (p<.001). Individual factors notably affected the expression and general study, teacher-related factors impacted reading, writing, and calculation, and environmental factors increased difficulties across all domains (p<.001). Better previous academic performance was associated with fewer difficulties (p<.05). Conclusion: The study recommends strategies to improve student attitudes, address individual, teacher-related, and environmental factors, and promote academic performance. Future research should explore different educational systems and the role of gender in learning difficulties.